2011
DOI: 10.1063/1.3615514
|View full text |Cite
|
Sign up to set email alerts
|

On the stationary macroscopic inertial effects for one phase flow in ordered and disordered porous media

Abstract: We report on the controversial dependence of the inertial correction to Darcy’s law upon the filtration velocity (or Reynolds number) for one-phase Newtonian incompressible flow in model porous media. Our analysis is performed on the basis of an upscaled form of the Navier-Stokes equation requiring the solution of both the micro-scale flow and the associated closure problem. It is carried out with a special focus on the different regimes of inertia (weak and strong inertia) and the crossover between these regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
117
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(138 citation statements)
references
References 68 publications
(112 reference statements)
19
117
1
1
Order By: Relevance
“…The general tactic is to derive and investigate additional terms added to Darcy law so that high Re laminar flow through porous media can be predicted on a global level. Also, turbulent flow through porous media has been treated theoretically and a quadratic dependence of the correction term for velocity has been derived in many studies (Skjetne and Auriault 1999;Lasseux et al 2011). In Jouybari et al (2016), the model by Nakayama and Kuwahara (1999) is extended to low Re turbulent flows by using a standard numerical model for a porous medium consisting of a staggered arrangement of square cylinders.…”
Section: Introductionmentioning
confidence: 99%
“…The general tactic is to derive and investigate additional terms added to Darcy law so that high Re laminar flow through porous media can be predicted on a global level. Also, turbulent flow through porous media has been treated theoretically and a quadratic dependence of the correction term for velocity has been derived in many studies (Skjetne and Auriault 1999;Lasseux et al 2011). In Jouybari et al (2016), the model by Nakayama and Kuwahara (1999) is extended to low Re turbulent flows by using a standard numerical model for a porous medium consisting of a staggered arrangement of square cylinders.…”
Section: Introductionmentioning
confidence: 99%
“…The directional decoupling and the diagonal property of the apparent permeability tensor have also been computationally demonstrated on a completely different REV geometry by Soulaine and Quintard (2014) . Conversely, Lasseux et al (2011) have carried out a two-dimensional study with fibers of square cross-section, finding that the off-diagonal terms are non-negligible and only about one order of magnitude smaller than the diagonal components. This result is a consequence of the non-rotationally-invariant geometry considered.…”
Section: (High)mentioning
confidence: 99%
“…For the purposes of the present paper, we must retain that Lasseux et al (2011) have parametrized the Forchheimer correction with the Reynolds number, and have found that the inertial correction is orders of magnitude smaller than the Darcy's term, at least before the turbulent regime sets in. Moreover, Lasseux and co-workers have studied how a Forchheimer tensor, F , depends upon the direction of the macroscopic forcing term with respect to the orientation of the square cross-section of the fibers, for Re d up to 30.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations